2020
DOI: 10.1038/s42004-020-0294-1
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolving the ultrafast H2 roaming chemistry and H3+ formation using extreme-ultraviolet pulses

Abstract: The time scales and formation mechanisms of tri-hydrogen cation products in organic molecule ionization processes are poorly understood, despite their cardinal role in the chemistry of the interstellar medium and in other chemical systems. Using an ultrafast extreme-ultraviolet pump and time-resolved near-IR probe, combined with high-level ab initio molecular dynamics calculations, here we report unambiguously that H 3 + formation in double-ionization of methanol occurs on a sub 100 fs time scale, settling pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 49 publications
4
58
0
Order By: Relevance
“…While the triplet remains stable for >1.5 ps of the NA-AIMD simulation, the longest-lived singlet trajectory dissociates after less than ∼400 fs due to the ultrafast roaming H 2 dynamics. 28 This in agreement with ultrafast H 3 + formation determined by time-resolved experimental studies. 28 , 46 In contrast, all of the 100 NA-AIMD trajectory simulations performed on the triplet ground state were found to resist CE.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…While the triplet remains stable for >1.5 ps of the NA-AIMD simulation, the longest-lived singlet trajectory dissociates after less than ∼400 fs due to the ultrafast roaming H 2 dynamics. 28 This in agreement with ultrafast H 3 + formation determined by time-resolved experimental studies. 28 , 46 In contrast, all of the 100 NA-AIMD trajectory simulations performed on the triplet ground state were found to resist CE.…”
supporting
confidence: 87%
“… 28 This in agreement with ultrafast H 3 + formation determined by time-resolved experimental studies. 28 , 46 In contrast, all of the 100 NA-AIMD trajectory simulations performed on the triplet ground state were found to resist CE.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…As a consequence of the displacement of hydrogen atoms, significant structural rearrangements could be triggered, leading to isomerization and thus alter the chemical functions of those molecules. In particular, for the ionic organic molecules, numerous studies have been conducted to elucidate the formation and evolution of ultrafast hydrogen migration through the sophisticated momentum imaging techniques [5][6][7][8][9][10][11][12][13][14][15][16][17] . It has been found that the hydrogen-migration channel can dominate over direct fragmentation in molecular cations 5 .…”
mentioning
confidence: 99%
“…In addition to the well-known single hydrogen migration, another more complicated process, that is, the double hydrogen migration has been proven to play a more important role than generally assumed in molecular fragmentation 6 . Furthermore, in some of those hydrogen-migration studies special attention has been paid to the reaction dynamics in the course of H 3 + formation [12][13][14][15][16][17] . H 3 + has been brought into research focus by its unique structural and dynamical nature and astronomical significance as the most important interstellar medium 18,19 .…”
mentioning
confidence: 99%